Students’ Perceptions of Computer-Based National Assessment in Improving Literacy and Numeracy - Sudiati, Sudiati (PPSDP International Journal of Education, 2025)
The purpose of this study was to evaluate students’ perceptions of Computer-Based National Assessment (ANBK) and how it impacts students’ literacy and numeracy skills. ANBK is one of the government’s efforts to evaluate students’ competencies using information technology. This study was conducted through direct observation and interviews with 30 students in grade V of elementary school. The results showed that the majority of students saw ANBK as an interesting tool and helped them learn. This study concluded that ANBK can help improve students’ basic skills in addition to improving their literacy and numeracy skills, although there were some problems with technology accessibility and students’ mental readiness. In the future, it is recommended to develop training programs and provide better technology facilities in schools to support better implementation of ANBK. Through this study, based on students’ perceptions of ANBK activities, it can be categorized as good or positive where students are able to find information, understand information, and evaluate and reflect in literacy activities, while in numeracy activities students can reason critically by using logic in solving problems in everyday life.